Nanocomposites of Polymeric Biomaterials Containing Carbonate Groups: An Overview. Issue 10 (17th July 2017) - Taraghi, Iman; Paszkiewicz, Sandra; Grebowicz, Janusz; Fereidoon, Abdolhossein; Roslaniec, Zbigniew
Abstract : Aliphatic polycarbonates based on nanocomposites are widely used in drug delivery, tissue engineering, electrolytes and biomedical instruments. One can synthesize these biopolymers by different methods. The nanoparticles can improve the physical and chemical properties of the biopolymers. Abstract : The modification of biomaterials using nanoadditives can lead to the development of novel materials for a wide variety of biomedical applications such as drug administration systems, tissue engineering, bioresistance coatings, and biomedical instruments. Moreover, a further improvement of mechanical and thermal properties of aforementioned biomaterials while maintaining their dimensional stability is a goal of major scientific researches. Aliphatic polycarbonates (APCs) containing carbonate groups such as poly(trimethylene carbonate), poly(propylene carbonate), poly(ethylene carbonate), poly(dimethyl trimethylene carbonate), etc., have become much more interesting compared to other biodegradable materials due to their unique physical and chemical properties. This review presents the effect of applying different kinds of nanoparticles (NPs) on the mechanical, thermal, and viscoelastic properties as well as dimensional stability and biocompatibility of APCs. The dispersion process of nanofillers within polymer matrices has been divided into two groups, solution and melt mixing techniques. Moreover, synthesis procedures of APC loaded NPs for drug delivery systems and electrospinning of nanofiber mats have also been reviewed. In order to clarify the effect of NPs on the overall characteristics of the APC biomaterials, the detailed mechanism of improving process have been extensively discussed.